2007
DOI: 10.1258/095646207781568420
|View full text |Cite
|
Sign up to set email alerts
|

The utility of screening for parasitic infections in HIV-1-infected Africans with eosinophilia in London

Abstract: The presence of asymptomatic eosinophilia in HIV patients has been demonstrated to have a wide variety of causes. Untreated parasitic infections in immunocompromised individuals can have potentially serious consequences. The utility of screening for parasitic infections in immigrant HIV-positive Africans with eosinophilia was investigated in a UK-based HIV clinic. HIV-positive African patients with eosinophilia were matched with HIV-positive African controls without eosinophilia. More than half of African HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
6
17
0
Order By: Relevance
“…More than 85% of children studied with and without intestinal helminths had eosinophilia thus the differences in these two groups were not statistically significant. The results obtained from this study were consistent with other studies and they also suggest the possibility of concurrent infections with helminths [23,24]. The low prevalence of helminths in the present study however suggested that the aetiology of eosinophilia in HIV infected individuals might be due to other aetiologies than helminths.…”
Section: Discussionsupporting
confidence: 92%
“…More than 85% of children studied with and without intestinal helminths had eosinophilia thus the differences in these two groups were not statistically significant. The results obtained from this study were consistent with other studies and they also suggest the possibility of concurrent infections with helminths [23,24]. The low prevalence of helminths in the present study however suggested that the aetiology of eosinophilia in HIV infected individuals might be due to other aetiologies than helminths.…”
Section: Discussionsupporting
confidence: 92%
“…2,3,10 Human immunodeficiency virus (HIV) infection may also present with eosinophilia, although helminth co-infection is still a more likely cause in this setting. 11 Eosinophilia has numerous non-infectious causes. Common non-infectious causes include drugs (non-steroidal anti-inflammatory drugs, beta-lactam antibiotics, nitrofurantoin and others), atopy (asthma, eczema and hay fever) and allergy.…”
Section: Introductionmentioning
confidence: 99%
“…In an HIV-infected population in the United Kingdom, screening for eosinophilia and parasites was undertaken in patients of African origin (18). Among the 51 patients with eosinophilia, 55% had positive parasite serology compared with 9% of control African HIV patients without eosinophilia.…”
mentioning
confidence: 99%
“…Thus, eosinophilia was a good marker for parasitic infection. However, 37% of patients with positive schistosomal serology had normal eosinophil counts when screened, indicating that infection may be present in the absence of eosinophilia (18). Microscopic diagnosis was made in only one of 89 specimens sent (47 urines and 42 stools), indicating poor test characteristics.…”
mentioning
confidence: 99%